Animal abuse and interpersonal violence : a psycho-criminological understanding - Chan, Heng Choon, 1981-; Wong, Rebecca Wing Yee, 1986- (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
'This book brings together leading scholars and practitioners from the United States, Europe, and Asia. The contributors come from different disciplines, including medicine, criminology, sociology, psychology, forensic sciences, and law. As a group, they have the background to discuss and conduct research in the area and to propose and critique theories and typologies of animal cruelty. In addition, they have the expertise to evaluate policy issues and to recommend best practices for protecting animals and intervening with those who abuse or neglect them'--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 05, 2023).
Added to collection customer.56279.3
Keywords: Animal welfare -- Psychological aspects; Violence; Criminal psychology; Criminal psychology; Violence; Electronic books